PENGARUH DEBT TO ASSET RATIO DAN CURRENT RATIO TERHADAP RETURN ON ASSET PADA PT HANJAYA MANDALA SAMPOERNA TBK PERIODE 2014-2023 - Ramdani, Julfikar; Al-Choir, Fikron (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to determine the effect of Debt to Asset Ratio (DAR) and Current Ratio (CR) on Return On Asset (ROA) at PT Hanjaya Mandala Sampoerna Tbk for the period 2014–2023. ROA is used as an indicator to measure the company’s effectiveness in utilizing its assets to generate profits. DAR reflects the company’s reliance on debt financing, while CR indicates its ability to meet short-term obligations. This research uses a quantitative approach with descriptive analysis. The data used are secondary data obtained from the company’s annual financial reports. Data analysis was conducted using multiple linear regression with the help of SPSS version 26, preceded by classical assumption tests. Hypothesis testing was carried out using t-test and F-test. The results show that partially, both Debt to Asset Ratio (DAR) and Current Ratio (CR) have no significant effect on Return On Asset (ROA), with significance values of 0.810 and 0.547 respectively (> 0.05). Simultaneously, DAR and CR also have no significant effect on ROA, as indicated by an F-value of 1.506, which is less than the F-table value of 4.74, and a significance level of 0.286 (> 0.05). The Adjusted R² value of 0.101 indicates that only 10.1% of the variation in ROA can be explained by DAR and CR, while the remaining 89.9% is influenced by other factors outside the model.